A novel preoperative risk score to predict lymph node positivity for rectal neuroendocrine tumors: An NCDB analysis to guide operative technique. Issue 6 (26th August 2019) - Gamboa, Adriana C.; Liu, Yuan; Lee, Rachel M.; Zaidi, Mohammad Y.; Staley, Charles A.; Russell, Maria C.; Cardona, Kenneth; Sullivan, Patrick S.; Maithel, Shishir K.
Abstract: Background/Objective: Staging and type of resection for rectal neuroendocrine tumors (R‐NETS) relies on preoperative identification of lymph node (LN) involvement. Study objective was to develop a Preoperative Rectal Stratification Score (PReSS) for LN‐positivity and to assess the association of PReSS with overall survival (OS). Methods: All patients in the National Cancer Database (2004‐2014) with non‐metastatic/nonfunctional R‐NETS were included. Tumor size was divided into three categories (<1, 1‐2, and ≥2 cm). Results: Among 383 patients, median age was 57 years, 52% were male (n = 200), median tumor size was 1.4 cm, 43% had positive LNs (n = 163). On univariate analysis, age > 60, poorly differentiated grade, depth of invasion past submucosa, and size >1 cm were associated with LN positivity. On multivariable analysis, depth of invasion past submucosa, and increasing tumor size >1 cm remained associated with LN positivity. As these can be determined preoperatively, incidence of LN positivity was determined for each combination of tumor size and depth of invasion. Each variable was assigned a score to create a PReSS of four groups (0‐3) associated with an increasing rate of LN‐positivity (PReSS group 0: 11%, 1: 38%, 2: 50%, 3: 78%, P < .01). PReSS correlated with 10‐year OS (PReSS 0: 90%; 1: 81%; 2: 59%; 3: 41%). Conclusion: For R‐NETS, depth of invasion and tumor size predict LN positivity and both can be obtained preoperatively. PReSS incorporates both variables and stratifies tumors into four risk groups of progressively increasing LN positivity and should be used to guide surgical approach.